ULTRASOUND ASSESSMENT OF ANATOMICAL STRUCTURES AT SELECTED ACUPOINTS ON THE HAND YANGMING LARGE INTESTINE MERIDIAN (Vietnam Journal of Community Medicine, 2026)
Objective: To characterize the underlying anatomical structures of selected acupoints on the Hand Yangming Large Intestine meridian using ultrasound.Subjects and methods: A pilot study was conducted in 30 healthy volunteers (aged 18-40 years, normal BMI). Selected acupoints on the upper limb were located according to standardized anatomical landmarks and examined using high-resolution ultrasound. Relevant muscles, bones, vessels, and nerves were identified, and their depths were measured from the skin surface.Results: Ultrasound enabled visualization of the anatomical layers beneath the acupoints. The depth from the skin to target structures varied by location. For example, at Hegu (LI4), the mean depth to the first dorsal interosseous muscle was 2.4 ± 0.49 mm; at Yangxi (LI5), the mean depth to the radial artery was 4.49 ± 0.73 mm. These findings provide quantitative guidance for estimating safe needling depth.Conclusion: Ultrasound is a useful, non-invasive tool for identifying anatomical structures beneath commonly used acupoints on the Hand Yangming Large Intestine meridian. It facilitates the determination of safe and effective needling depth. These findings may enhance the accuracy and safety of acupuncture practice
Keywords: Acupuncture, acupoints, ultrasound, Hand Yangming Large Intestine meridian.